Non-Viral Delivery of RNA Gene Therapy to the Central Nervous System - Ellen S. Hauck; James G. Hecker (MDPI AG, 2022)
Appropriate gene delivery systems are essential for successful gene therapy in clinical medicine. Lipid-mediated nucleic acid delivery is an alternative to viral vector-mediated gene delivery and has the following advantages. Lipid-mediated delivery of DNA or mRNA is usually more rapid than viral-mediated delivery, offers a larger payload, and has a nearly zero risk of incorporation. Lipid-mediated delivery of DNA or RNA is therefore preferable to viral DNA delivery in those clinical applications that do not require long-term expression for chronic conditions. Delivery of RNA may be preferable to non-viral DNA delivery in some clinical applications, since transit across the nuclear membrane is not necessary, and onset of expression with RNA is therefore even faster than with DNA, although both are faster than most viral vectors. Delivery of RNA to target organ(s) has previously been challenging due to RNA's rapid degradation in biological systems, but cationic lipids complexed with RNA, as well as lipid nanoparticles (LNPs), have allowed for delivery and expression of the complexed RNA both in vitro and in vivo. This review will focus on the non-viral lipid-mediated delivery of RNAs, including mRNA, siRNA, shRNA, and microRNA, to the central nervous system (CNS), an organ with at least two unique challenges. The CNS contains a large number of slowly dividing or non-dividing cell types and is protected by the blood brain barrier (BBB). In non-dividing cells, RNA-lipid complexes demonstrated increased transfection efficiency relative to DNA transfection. The efficiency, timing of the onset, and duration of expression after transfection may determine which nucleic acid is best for which proposed therapy. Expression can be seen as soon as 1 h after RNA delivery, but duration of expression has been limited to 5-7 h. In contrast, transfection with a DNA lipoplex demonstrates protein expression within 5 h and lasts as long as several weeks after transfection.